Theory of Mind and Language in Childhood Epilepsy. Issue 2 (23rd December 2019) - Bailey, Katharine; Im‐Bolter, Nancie
ABSTRACT: We examined theory of mind (ToM; mental state understanding) and language in children with epilepsy (EP; n  = 10; mean age = 9.92, SD  = 2.34) and with typical development (TD; n  = 20; mean age = 10.05, SD  = 2.08). The EP group demonstrated worse ToM compared to the TD group ( t (28) = −1.11, p  = .28, d  = .44) but differences did not persist when controlling for language. Syntactic language was correlated with ToM in the EP group (rho (10) = .79, p < .01). This study confirms language is important for ToM in a group of children with a neurological disorder and indicates that children with epilepsy are at risk for difficulties in understanding the mental states of others due to their language deficits. This may help to explain the social difficulties these children have with their peers.